Perilaku Komunikasi Nonverbal Anak Autis dalam Proses Belajar di Sekolah Luar Biasa Autisma Mutiara Bangsa Pratama - Zofa, Monica Ramadhani; Marlina, Marlina (Universitas Negeri Padang, 2024)
This study aims to determine the nonverbal communication behavior of autistic children in the learning process at SLB Autisma Mutiara Bangsa Pratama. The focus of this research is to describe how the nonverbal communication behavior of autistic children and what the meaning of nonverbal communication behavior of autistic children is in the learning process at SLB Autisma Mutiara Bangsa Pratama. The results of the study show that the forms and meanings of nonverbal communication behavior in autistic children are very diverse, in the form of 1) facial expressions smiling which means happy, 2) body movements such as supporting the chin with the hand means bored, hitting the table means angry, 3) touching (haptika) is like holding the teacher's hand and holding out the teacher's hand means asking the teacher to pray, clapping the teacher's hand and waving her hand means not wanting to learn what is being studied, touching the teacher's hand and pulling the teacher's hand means wanting something.